To the question of labour law duties in the Republic of Kazakhstan - Zhumabayeva, A.B. (Bulletin of the Karaganda University “Law Series”, 2021)
The article analyzes the approaches of some Soviet and modern scientists to the concept of duties, the current labour legislation within the legal status of the parties to labour relations. The purpose of the study is to consider the category of “duty” in the field of labour law as the concept of labour obligations of an employee and an employer. Since duty is a complex, multifaceted category closely related to the rights of the individual, rights cannot themselves be realized without the corresponding obligations to fulfil and secure them. Soviet times are characterized by great attention to the concept of duty in the field of labour, since work without duty to it was impossible. The duty of each person at work was part of an ideological mechanism. The modern approach to the concept of duty in labour law is more revealed through the mechanism of voluntary agreement between the employee and the employer on mutual rights and obligations. Author examined the issues of liability of the employee through the prism of the employer's obligations. Certain provisions of the Labour Code of the Republic of Kazakhstan (LC RK) need to be clarified and amended. The authors provided proposals for improving the current LC RK. It was offered to establish the limits of material liability of the employee and return the norm of the article to the 2007 LC RK. Regarding remote workers, it was suggested to distinguish the differences between the concept of remote workers and temporary remote workers, to establish minimum standards and requirements for the employer to ensure the safety of property entrusted to the remote employee.